UTILIZATION OF TURMERIC AND DRAGON FRUIT PEEL EXTRACTS AS NATURAL ANTIBIOTICS ON BROILER CARCASS CUT PERCENTAGE - A.T., Hardini; Umiarti, A.T.; Wirapartha, M. (Jurnal Peternakan Tropika; Vol 12 No 4 (2024): Vol. 12 No. 4 Tahun 2024; July - August, 2024)
This study aims to determine how the effect of giving turmeric extract, dragon fruit peel and a mixture of both on the percentage of broiler carcass cuts in drinking water, this study was conducted for 28 days. The design used is a completely randomized design (CRD) consisting of four treatments, four replicates, and each replicate consists of five broilers. The treatments consisted of P0 drinking water without a mixture of turmeric extract and dragon fruit peel (control), P1 drinking water with 4% turmeric extract, P2 drinking water with 4% dragon fruit peel extract, P3 drinking water with 2% turmeric extract and 2% dragon fruit peel extract. The observed variables were carcass weight, breast percentage, thigh percentage, back percentage and wing percentage. The results of this study showed that the provision of turmeric extract, with a concentration of 4% in drinking water showed significant (P < 0.05) in increasing the weight of broiler carcasses. The results of the study concluded that giving turmeric extract P1 with a concentration of 4% was able to increase carcass weight while giving 4% dragon fruit peel extract P2 was not able to increase broiler carcass weight. giving 2% turmeric extract and 2% dragon fruit peel P3 was not able to increase broiler carcass weight.